Desain Sistem Informasi Magang Terintegrasi Berbasis Web Menggunakan UML: Fase Desain dalam Metode Waterfall - Muhammad Richie Hadiansah; Muhammad Irwan Padli Nasution (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
This study designs a web-based internship information system that integrates internship administration for interns, field supervisors, and administrators. This system is designed to address manual internship management issues, such as recording errors, delays in obtaining validation, and difficult participant activity monitoring. The development method used is Waterfall, with the research focus only on the design stage using Unified Modeling Language (UML) consisting of use case diagrams, activity diagrams, sequence diagrams, and Class Diagrams. System planning aims to obtain a structured design model, in which there are multi-role login features, participant profile management, attendance and logbook filling, final report uploads, assessments carried out by supervisors, and account management by admins. The result of this study is a system design that can be used as a reference for further development aimed at digitizing internship management.